Identifying the causes of the barriers that prevent fire safety projects from being installed: evidence from Nirvana Engineering Solution Limited - Nazrul, Nadira Binte (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.